Understanding a Switched Reluctance Motor Control and Analysis Methods Using Matlab/simulink - (:unkn) unknown (IEEE, 2021)
Teaching the motor control methods and the analysis with simulation is very important for engineering education. The simulation platforms, such as MATLAB/Simulink, are necessary for students to develop and analyze various motor control algorithms, particularly in electrical machines courses. This study focused on the PID controller, its features and analysis for a switched reluctance motor drive using the MATLAB/Simulink software program. It is a special motor in electrical motors. We used the mathematical models, tuning methods and bode diagrams to investigate the effects and property of the controller parameters and system stability on the switched reluctance motors, which is already in the educational tools of the MATLAB software library.
Keywords: Bode; controller; education; MATLAB/Simulink; PID; SRM